2020
DOI: 10.1155/2020/2353827
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Flame-Retardant Properties of Nanocomposite Based on Epoxy Resin Combined with Epoxidized Linseed Oil, Which Has the Presence of Nanoclay and MWCNTs

Abstract: One of the main disadvantages of epoxy resins is brittleness and flammability, which is one of the biggest threats and the reason for limiting advanced applications. In this study, Epikote 240 (EP) epoxy resin was plasticized with epoxidized flaxseed oil (ELO) at different concentrations (EP/ELO ratios 95/5; 90/10; 85/15; 80/20; 75/25). Then, nanoclay additives and MWCNTs are simultaneously dispersed into the EP/ELO blend by using ultrasonic vibration. The dispersion of ELO and nanoclay additives (nanoclay and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In addition to the study of using fibers of natural origin as reinforcement for polymer composite materials, unidirectional woven fabrics and plain woven fabrics have also been studied by Mostafa et al [19,20]. In order to improve the mechanical and fireproof properties of composite materials, in addition to using plant fibers, artificial fibers, etc., many works have also used typical environmentally friendly additives such as fly ash [21,22], nanoclay [23], multiwalled carbon nanotubes and especially the hybrid between those admixtures: nanoclay/multiwalled carbon nanotubes (MWCNTs) [24][25][26] and MWCNTs/fly ash [27], and nanoclay/fly ash [28]. e source of banana fiber is the banana stem (banana tree skin); waste is abundant in many parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the study of using fibers of natural origin as reinforcement for polymer composite materials, unidirectional woven fabrics and plain woven fabrics have also been studied by Mostafa et al [19,20]. In order to improve the mechanical and fireproof properties of composite materials, in addition to using plant fibers, artificial fibers, etc., many works have also used typical environmentally friendly additives such as fly ash [21,22], nanoclay [23], multiwalled carbon nanotubes and especially the hybrid between those admixtures: nanoclay/multiwalled carbon nanotubes (MWCNTs) [24][25][26] and MWCNTs/fly ash [27], and nanoclay/fly ash [28]. e source of banana fiber is the banana stem (banana tree skin); waste is abundant in many parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…As for the flame-retardant properties, the research results in this work show that there is almost no effect when mixed at different concentrations. If the application is in the field of building materials with fire resistance, it is possible to mix other flame-retardant additives to have a resonant performance [31].…”
Section: Fire-retardant Propertymentioning
confidence: 99%
“…To improve the mechanical properties and fire retardancy of epoxy materials, environmentally friendly additives have been studied. Additive nanoclay, multiwalled carbon nanotubes are incorporated into epoxy resin to improve mechanical properties while increasing fire retardancy [13][14][15]. Besides, fly ash waste from thermal power plants is also recycled by using it as an additive to composite materials to improve fire resistance [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, multi-walled carbon nanoadditive has been researched by many scientists around the world to manufacture flame retardant materials. e results showed that with only 0.02 wt.% MWCNTs dispersed in epoxy resin the flame retardation was significantly improved, and mechanical properties improved [9,10]. Nikolas Sabbattini has studied a paint containing clay or plaster to cover theaters in Italy is fire resistant.…”
Section: Introductionmentioning
confidence: 99%